A Comparison of 2 Online Parent Skills Training Interventions for Early Childhood Brain Injury: Improvements in Internalizing and Executive Function Behaviors. Issue 2 (March 2019) - Aguilar, Jessica M.; Cassedy, Amy E.; Shultz, Emily L.; Kirkwood, Michael W.; Stancin, Terry; Yeates, Keith Owen; Taylor, H. Gerry; Wade, Shari L.
Abstract : Objective: To examine the effectiveness of a web-based parenting intervention (Internet-Based Interacting Together Everyday: Recovery After Childhood TBI [I-InTERACT]) and an abbreviated version (Express) in reducing executive dysfunction and internalizing problems among young children following traumatic brain injury (TBI). Method: Parents of 113 children (ages 3-9 years) who had sustained a TBI were randomized to 1 of 3 treatment groups: I-InTERACT, Express, or an Internet Resource Comparison (IRC) group. Parents who participated in either I-InTERACT or Express completed self-guided web sessions and received live coaching of their parenting skills via videoconferencing with a therapist. I-InTERACT included additional psychoeducation, stress management, and family communication skills (eg, marriage, grief, pain, and sleep). Analyses of covariance were utilized to compare the groups on parent-reported executive function behaviors (ie, Behavior Rating Inventory of Executive Function) and internalizing symptoms (ie, Child Behavior Checklist) at baseline and 6 months. Results: Parents who participated in Express reported significantly lower levels of executive dysfunction than those in I-InTERACT, β = −0.49; t (2, 73) = −2.47, P = .048, and significantly lower levels of withdrawal than those in the IRC group, β = −0.44; t (2, 74) = −2.22, P = .03. The Express group did not significantly differ from the IRC group on executive function behaviors or the I-InTERACT group on internalizing problems, all P > .05. Children with more problems at baseline, families with lower education levels, and parents with more symptoms of depression benefited most. Conclusion: A brief, online parent training intervention may be efficacious in improving executive dysfunction and internalizing problems following early TBI, particularly among children of lower socioeconomic status or with existing behavioral concerns.